Target enrichment of long open reading frames and ultraconserved elements to link microevolution and macroevolution in non‐model organisms - (:unkn) unknown (My University, 2022)
Despite the increasing accessibility of high-throughput sequencing, obtaining highquality genomic data on non-model organisms without proximate well-assembled and annotated genomes remains challenging. Here, we describe a workflow that takes advantage of distant genomic resources and ingroup transcriptomes to select and jointly enrich long open reading frames (ORFs) and ultraconserved elements (UCEs) from genomic samples for integrative studies of microevolutionary and macroevolutionary dynamics. This workflow is applied to samples of the African unionid bivalve tribe Coelaturini (Parreysiinae) at basin and continent-wide scales. Our results indicate that ORFs are efficiently captured without prior identification of intron-exon boundaries.
Keywords: African Research